Investigation of the specific toxicity of an antibacterial veterinary drug based on amoxicillin - Y. V. Horiuk; R. M. Sachuk (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
The article presents the results of studying the subacute toxicity of the veterinary drug “Amoksidev 60” on white rats. The drug “Amoksidev 60” is a powder for preparing an oral solution. 1 g of the drug contains the active substance: amoxicillin – 500 mg (as amoxicillin trihydrate – 573 mg); auxiliary substances: anhydrous citric acid – up to 1 g. The veterinary medicinal product is used to treat pigs, in diseases of the digestive tract and respiratory organs caused by microorganisms sensitive to amoxicillin. As a result of the research, it was established that the oral administration of the drug “Amoksidev 60” (according to amoxicillin) with drinking water to white rats, in doses of 20.0 and 100.0 mg/kg of body weight, for 10 days, does not cause hemo-, hepatotoxic and nephrotoxic effects on the body of laboratory animals, under the conditions of a subacute toxicological experiment. Whereas when the drug was administered at a dose of 200.0 mg/kg of body weight, 10 days after the start of drug administration, a decrease in total hemoglobin content by 7.3 %, hematocrit by 6.7 %, and the number of erythrocytes was recorded in the blood of rats by 8,8 % Р < 0.05) and in the blood serum – an increase in the activity of ALT, AST and urea concentration by 16,3; 17.8 and 10.9 % (Р < 0.05), respectively. However, 7 days after stopping the administration of the drug “Amoksidev 60” with drinking water in a 10-fold dose, the hematological and biochemical parameters of the rats' blood approached the control level. Further studies will be the next stage of pre-registration tests aimed at studying the toxicity of the drug “Amoksidev 60” during repeated administrations to pigs (subacute toxicity after oral administration), which is a mandatory material of the “Safety and residue studies” section of the dossier for this medicinal product.